2014
DOI: 10.1371/journal.pone.0103092
|View full text |Cite
|
Sign up to set email alerts
|

Non-Invasive Pneumococcal Pneumonia in Portugal—Serotype Distribution and Antimicrobial Resistance

Abstract: There is limited information on the serotypes causing non-invasive pneumococcal pneumonia (NIPP). Our aim was to characterize pneumococci causing NIPP in adults to determine recent changes in serotype prevalence, the potential coverage of pneumococcal vaccines and changes in antimicrobial resistance. Serotypes and antimicrobial susceptibility profiles of a sample of 1300 isolates recovered from adult patients (≥18 yrs) between 1999 and 2011 (13 years) were determined. Serotype 3 was the most frequent cause of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(36 citation statements)
references
References 27 publications
(54 reference statements)
1
35
0
Order By: Relevance
“…These publications are summarised in online Supplementary Table S1. Of the included publications, 31 were prospective or surveillance [5,21,25,28,30,33,38,40,41,46,49 National population-based epidemiologic surveillance data for pneumonia were available from Norway [54], Portugal [58] and Spain [59,75,77]. As observed by Tichopad and colleagues [29], epidemiologic data in Central and Eastern Europe were predominantly collected from hospital settings, and there was a lack of data on outpatient CAP, with the authors instead using inpatient-to-outpatient ratios from a retrospective chart review to estimate outpatient incidence in the Czech Republic, Hungary, Poland and Slovakia.…”
Section: Studies Includedmentioning
confidence: 99%
“…These publications are summarised in online Supplementary Table S1. Of the included publications, 31 were prospective or surveillance [5,21,25,28,30,33,38,40,41,46,49 National population-based epidemiologic surveillance data for pneumonia were available from Norway [54], Portugal [58] and Spain [59,75,77]. As observed by Tichopad and colleagues [29], epidemiologic data in Central and Eastern Europe were predominantly collected from hospital settings, and there was a lack of data on outpatient CAP, with the authors instead using inpatient-to-outpatient ratios from a retrospective chart review to estimate outpatient incidence in the Czech Republic, Hungary, Poland and Slovakia.…”
Section: Studies Includedmentioning
confidence: 99%
“…Therefore, it is a reasonable assumption that the serotype distribution of adult pneumococcal pneumonia in Japan will change during the post-PCV13 period (9,10). Sustaining a nationwide surveillance system and periodic reporting is therefore crucial for investigating the effect of routine PCV13 vaccinations for children on pneumococcal serotype distribution in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have reported that the serotype distribution among adult invasive pneumococcal disease (IPD) cases is influenced by the introduction of PCV vaccination in children (5-7), which is called "serotype replacement." However, few studies have shown serotype replacement in cases of adult pneumococcal pneumonia, all of which were from Europe (8)(9)(10). Because serotype distribution differs between pneumonia cases and IPD cases (8,10), it is crucial to clarify the impact of PCV introduction in children on the serotype distribution in adult pneumonia, which has a far greater disease burden than does IPD.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations